Choledocholithiasis during Pregnancy: Multimodal Approach Treatment - Hendra Koncoro; Cosmas Rinaldi Lesmana; Benny Philipi (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Pregnancy is an important risk factor for growth of choledochal stones. Since choledocholithiasis encountered during pregnancy, which is also a possible cause of pancreatitis and cholangitis, may be the reason for serious morbidity and mortality both for the mother and the fetus, it should be treated. In this article, the results and reliability of endoscopic retrograde cholangiopancreatography (ERCP) application on a pregnant woman accompanied with percutaneous biliary procedures are presented.            We report a case of 33-year-old woman at 19th week of gestation with cholestatic jaundice due to a common bile duct (CBD) stone managed by endoscopic retrograde cholangiopancreatography (ERCP). The patient had post ERCP pancreatitis which resolved with medical management. Percutaneous cholecystostomy was also performed to control source of infection in the gallbladder.            ERCP is the first procedure that will be preferred in the treatment of choledocholithiasis in pregnancy with the right indications provided that proper precautions have been taken. Possible harmful effects of ionized radiation on fetus during fluoroscopy should be minimalized by giving in short periods and low doses.Keywords: